New Effect for Faraday Tensor for Biharmonic Particles in Heisenberg Spacetime - Korpinar, Talat; Asil, Vedat (Springer/Plenum Publishers, 2015)
The present study deals with Heisenberg spacetime representing the component of Faraday tensor. We express some interesting relations about Faraday tensor in the Heisenberg spacetime. Finally, we illustrate the components of Faraday tensor in the Heisenberg spacetime.
Keywords: Energy; Bienergy; Heisenberg spacetime; Faraday tensor; Lorentz equation